Priority Directions Of Improving The Geography Of The Spread Of Virus Diseases And The Nosogeographic Situation In Uzbekistan (Eurasian Journal of History, Geography and Economics, 2024)
In this article, the geography of the distribution of viral diseases and ways to improve the nosogeographical environment are analyzed in detail, the main factors of the spread of hepatitis from viral diseases, how they are related to climate, geographical location and human activity are considered. Viral hepatitis and their spreading mechanisms, as well as environmental conditions that play a role in the epidemic of diseases, are analyzed. The article also defines important directions for the prevention and reduction of viral hepatitis diseases based on modern scientific research.